Assessment of Risk Factors, Health Related Quality of Life among Hypertensive Patients in Primary Health Care Center- Iraq-2020 - Ban Nadhum Abdul-Fatah; Yaseen Taha Sarhan (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background; Chronic diseases disturb life expectancies, (1) that effect psychological, social, and economical status.(2) The present study evaluated the risk factors and health related quality of life (HRQL) among hypertensive patients. Objectives: Assessment of risk factors, (HRQL) among hypertensive patients in ALAndalus primary health care center in AL-Ramadi city during the period January–March-2020. Materials &methods: a cross sectional study involved 100 hypertensive patients using Flanagan Quality of Life Scale in AL- Andalus primary health care center in AL-Ramadi city during the period January–March-2020. Results: The study revealed that 66% of the patients were males and 67% of them were over 55 years, working, graduated, smokers and from urban area. About half of females were over 55 years that 42% of them completed 2nd school but all of them were not-working and from rural area. Sixty percent of persons had high blood cholesterol level with average mean was 240, 220 mg/dl for males & females respectively, the same percent had cardiac disease while, 40% of them had diabetes mellitus for both sexes. The average body mass index was 39, 36 among males and females respectively. Thirty eight percent of patients had good and very good material and physical well-being with average mean 2.5 ± (0.5), while only twentyfour percent had good and very good relationships with other people, the average mean was 2.0 ± (0.5) with statistical significance with sex. Thirty-two percent of persons had good and very good social, community, and civic activities with average mean 2.4 ± (1.0) and significant with sex. Only twenty-eight percent of persons had personal development and fulfillment with average mean 2.5 ± (0.4) and significant with sex, while forty-two percent of them had recreation with average mean 3.0 ± (1.0) that also significant with sex. Conclusion: High risk factors for both sexes and poor quality of life, mostly among female hypertensive patients.